Living the Qur'an in the Numpang Sedekah Tradition: Almsgiving Practice in the Muara Karang Village Community, Empat Lawang Regency - Agustini; Yuhaswita; Refileli; Jonsi Hunadar; Sultan Gholand Astapala; Dewi Aprilia Ningrum (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This research diverges from the phenomenon that occurs in the community of Muara Karang Village, which is undoubtedly influenced by the religious beliefs they hold. These beliefs are derived from the Qur'an and the Hadith of the Prophet, which form the interaction of society with the Qur'an. The text of the Qur'an is used as a practice in the execution of traditions. The purpose of this investigation is to portray the tradition of the Lintang community of Muara Karang Village, Pendopo District, Empat Lawang Regency, which utilizes the Qur'an as its foundation for the traditional procession of